2019
DOI: 10.1002/cncr.32063
|View full text |Cite
|
Sign up to set email alerts
|

Noncancer mortality among adolescents and young adults with cancer

Abstract: Background Relative to the general population, cancer patients and survivors may have an elevated risk of mortality from noncancer causes, such as cardiovascular disease and infections, but few studies have examined rates of noncancer mortality among patients diagnosed as adolescents and young adults (AYAs) (ages 15‐39 years). Methods The Surveillance, Epidemiology, and End Results database was used to identify AYA patients who were diagnosed with a first malignant cancer between 1973 and 2015. Rates of mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 28 publications
7
44
0
Order By: Relevance
“…Another more recently researched cause of mortality for patients with cancer is suicide, with an emphasis on emotional distress and anxiety in particular, although this is understudied 31,35 . Our study confirms previous reports showing that there is a relatively high rate of suicides amount pediatric cancer survivors, particularly for survivors of Hodgkin lymphoma and gonadal germ cell tumors.…”
Section: Discussionsupporting
confidence: 85%
“…Another more recently researched cause of mortality for patients with cancer is suicide, with an emphasis on emotional distress and anxiety in particular, although this is understudied 31,35 . Our study confirms previous reports showing that there is a relatively high rate of suicides amount pediatric cancer survivors, particularly for survivors of Hodgkin lymphoma and gonadal germ cell tumors.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have analyzed the causes of death among patients with different types of cancer [ 9 , 10 ]. Further, several investigations have also reported the causes of death in specific cancer types such as breast cancer, and head and neck cancer [ 11 , 12 ], or among a subgroup of patients such as adolescents and young adults [ 13 ]. Unfortunately, no detailed research has been performed on colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] One recent study using Surveillance, Epidemiology, and End Results data reported that AYA cancer survivors have a higher risk of death due to infection, cardiovascular disease, and renal disease. 20 Among childhood cancer survivors, the risk of death due to primary cancer recurrence is high within the first 10 years after diagnosis but decreases thereafter, whereas the risk of death due to pulmonary or cardiac causes or to secondary malignancy initially is low but then increases. 21,22 An improved understanding of the ways in which causes of death among AYA cancer survivors change over time is needed to identify the main drivers of improved survival and reduce persistent disparities in long-term survival between AYA cancer survivors and the general population.…”
Section: Discussionmentioning
confidence: 99%